مستوى السلوك الإبداعي وعلاقته بالولاء التنظيمي - فارسي, إبراهيم الخليل (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت هذه الدراسة إلى الكشف عن مستوى السلوك الإبداعي والولاء التنظيمي، لدى عينة من عمال المؤسسة الوطنية للصيانة والنقل بمدينة الاغواط والتعرف على طبيعة العلاقة بينهما ومعرفة فيما لو كان هناك فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) في السلوك الإبداعي والولاء التنظيمي لدى العاملين تعزى للمتغيرات (الجنس، الاقدمية). ولقد تم الاعتماد على اداتين للقياس أداة خاصة باسلوك الإبداعي واداة خاصة بالولاء التنظيمي وتم توزيعها على عينة عشوائية قوامها 32 فردا، من مجتمع العينة معتمدين في ذلك على المنهج الوصفي الارتباطي لملائمته الدراسة الحالية، وبعد اخضاع النتائج للمعالجة الإحصائية، اسفرت النتائج على: وجود مستوى منخفض للسلوك الإبداعي كما سجلت النتائج وجود مستوى مرتفع للولاء التنظيمي. الكلمات المفتاحية: السلوك الإبداعي؛ الولاء التنظيمي. Abstract: This study aimed to reveal the level of creative behavior and organizational loyalty, among a sample of workers of the National Corporation for Maintenance and Transport in Laghouat, to identify the nature of the relationship between them, and to know if there were statistically significant differences at the level of significance (0.05) in the creative behavior and organizational loyalty of the workers that were attributed for variables (gender, seniority). We have relied on two measuring tools, a tool for creative behavior and a tool for organizational loyalty, and they were distributed to a random sample of 32 individuals, from the sample community, relying on the descriptive correlative approach to suit the current study, and after subjecting the results to statistical treatment, the results resulted in: The presence of a low level for creative behavior, the results also recorded a high level of organizational loyalty
لدى عينة من عمال المؤسسة الوطنية للنقل سوناطراك
مقال
Keywords: السلوك الابداعي، الولاء التنظيمي; Creative behavior; organizational loyalty